Evaluating the Economic Impact of Special Economic Zones on GDP per Capita in China: A Difference-in-Differences Approach - Sheng, Yonghe; Yu, Yue (Transactions on Economics, Business and Management Research, 2024)
This study investigates the economic impact of Special Economic Zones (SEZs) on GDP per capita (GDPc) in China using a Difference-in-Differences (DiD) approach. By comparing cities designated as SEZs with those that were not, the analysis assesses the effect of SEZ policies implemented at different times. The results indicate that SEZs have a robust, positive, and significant impact on GDPc, with earlier treated cities experiencing a higher positive effect than later treated ones. This underscores the importance of timely policy implementation in maximizing economic benefits. Robustness checks, including two-way fixed effects and state-specific linear time trends, reinforce the reliability of the findings. However, the study acknowledges several limitations, such as the potential weakening of the parallel trends assumption over time, the use of a binary treatment variable, and the specific context of China's SEZ policy which may limit generalizability. Future research should address these limitations by exploring continuous treatment variables, incorporating additional control variables, and conducting comparative studies in different contexts. Despite these limitations, the findings provide valuable insights into the economic effects of SEZs and contribute to the broader understanding of regional economic development policies.